An Analysis towards Teachers’ Perception on their Schools’ Conduciveness to English Language Learners’ Success at SMA Negeri 3 Kota Ternate - Melinda Marus; Sahrun Sudirman (Jurnal Langua, 2020)
This study aims at the perception of English teachers on the influence of the conducive environment of the school on students' English learning achievement (SMA Negeri 3 Ternate City, Indonesia). By involving two English teachers at the school, researchers conducted interviews to obtain the required information. By using content analysis, researchers find a variety of very interesting information to pay attention to. In fact, the level of environmental conduciveness in the school also affects the level of achievement of English learning. The contributing factors are differences in students' linguistic backgrounds, lack of technology support, and low time allocation for English subjects. Researchers also found that differences in culture, race, and religion did not affect the conduciveness of the English learning environment at all so that these variables were not relevant to student learning outcomes.